Hubungan antara Attitude toward Singlehood dengan Kesejahteraan Psikologis Wanita Lajang Dewasa Awal - Sheravina, Chaterine Beta Chandra; Rahayu, Maria Nugraheni Mardi (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the relationship between attitudes toward singlehood and psychological well-being among early adult single women. This quantitative correlational study involved 346 unmarried single women aged 25-40 years, who were neither nuns nor bhikkhunis, selected using a snowball sampling technique. Attitudes toward singlehood were measured using the Attitude Toward Singlehood Scale (α = 0.931), while psychological well-being was assessed using the Psychological Well-Being Scale (α = 0.895). The results showed a significant positive relationship between attitudes toward singlehood and autonomy (r = 0.132; p < 0.05), as well as significant negative relationships with personal growth (r = –0.140; p < 0.05) and purpose in life (r = –0.143; p < 0.05). No significant relationships were found with environmental mastery, positive relations with others, or self-acceptance. Overall, these findings indicate that positive attitudes toward singlehood strengthen autonomy but are associated with lower personal growth and a diminished sense of purpose in life.